Long-Term Performance of Point-of-Care Hemoglobin A1c Assays. (November 2016) - Paknikar, Sujaytha; Sarmah, Rohan; Sivaganeshan, Losika; Welke, Adam; Rizzo, Al; Larson, Kirk; Rendell, Marc
Background: Point-of-care (POC) testing of HbA1c is used as a time-efficient tool to improve treatment and management planning for diabetes in the clinic setting. HbA1c values are the basis for monitoring ongoing response to treatment and to make adjustments to diabetes therapy. Yet, there is ongoing controversy as to the accuracy of POC assays. Diabetes is a lifelong disease, so comparability of results over a long period of time is needed to follow the response to treatment. Methods: We compared the Afinion™ automated boronate affinity assay and the DCA Vantage immunoassay-based POC techniques to the Tosoh G8 and Bio-Rad Variant II ion-exchange high-performance liquid chromatography (HPLC) central laboratory methods in a study lasting 3 years. College of American Pathology Survey results and American Proficiency testing were utilized to assess the external validity of the POC techniques. Results: Despite high correlations among the 4 techniques, there were significant and variable differences obtained over time. The Biorad values varied from 0.1 to 0.4% higher than the Afinion values. The DCA results were usually higher than the Afinion values, but fell below the Afinion results in the last 6 months of our study. Both POC techniques gave systematically lower values than the Tosoh measurements, and both the POC and the central laboratory measurements showed variable differences from the National Glycohemoglobin Standardization Program values over the duration of this study. Conclusions: All who rely on POC methods as well as on central laboratory measurement of HbA1c must understand the potential limitations of these assays. The assessment of diabetes blood sugar control should proceed from the evaluation of HbA1c combined with review of plasma glucose and of self-monitored blood glucose values.